PENGARUH KUALITAS JASA DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN INDIHOME - Agus Salim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
Technological progress is one of the important factors that can advance a country. One of the fastest growing technologies in the last decade is the Internet. According to market research institute e-Marketer, Internet users in the world is estimated to reach 3.6 billion in 2018. Internet users in Indonesia in 2016 has reached 132.7 million people based on a survey conducted by the Association of Internet Network Providers Indonesia. Theories used to support this research are service quality, brand image, and customer satisfaction. Sampling method in this research is non probability sampling with judgment sampling technique. The procedure used for data processing using SPSS 23.0. The spread of questionnaires was done online with 120 respondents using IndiHome Internet service. The result of research shows that service quality and brand image have positive effect to customer satisfaction. The conclusions of this study indicate that IndiHome customers are not satisfied with the Service Quality and Brands that are normal. Keywords: Servqual, Brand Image, Customer Satisfaction